#WeareUnited, cyber-nationalism during times of a national crisis: The case of a terrorist attack on a school in Pakistan. Issue 1 (February 2019) - Kalim, Salma; Janjua, Fauzia
Seeing language as a social practice and national identities as a product of discourse, the study intends to analyze discursive practices employed on social media to create the discourses of sameness and difference in times of national crisis. Following the discourse historical approach, I have illustrated how argumentative strategies and topos have been strategically employed to draw boundaries between Us and Them . In this exploration of exclusionary rhetoric, I have also underlined the use of images, memes and hashtags in the meaning-making process. The study illustrates not only the ways in which the discourse of national identities are constructed, but also how the existing pillars of Pakistani national identities have been transformed and dismantled on social media following a national tragedy. By investigating the digital practices and discourses, this study seeks to understand the construction of Pakistani national identities from bottom-up discourses.